Optimization of Antimicrobial Stewardship Programs Using Therapeutic Drug Monitoring and Pharmacokinetics–Pharmacodynamics Protocols: A Cost-Benefit Review. Issue 2 (2nd April 2023) - Telles, João Paulo; Morales, Ronaldo; Yamada, Carolina Hikari; Marins, Tatiana A.; D'Amaro Juodinis, Vanessa; Sztajnbok, Jaques; Silva, Moacyr; Bassetti, Bil Randerson; Albiero, James; Tuon, Felipe Francisco
Abstract : Purpose: Antimicrobial stewardship programs are important for reducing antimicrobial resistance because they can readjust antibiotic prescriptions to local guidelines, switch intravenous to oral administration, and reduce hospitalization times. Pharmacokinetics–pharmacodynamics (PK-PD) empirically based prescriptions and therapeutic drug monitoring (TDM) programs are essential for antimicrobial stewardship, but there is a need to fit protocols according to cost benefits. The cost benefits can be demonstrated by reducing toxicity and hospital stay, decreasing the amount of drug used per day, and preventing relapses in infection. Our aim was to review the data available on whether PK-PD empirically based prescriptions and TDM could improve the cost benefits of an antimicrobial stewardship program to decrease global hospital expenditures. Methods: A narrative review based on PubMed search with the relevant studies of vancomycin, aminoglycosides, beta-lactams, and voriconazole. Results: TDM protocols demonstrated important cost benefit for patients treated with vancomycin, aminoglycosides, and voriconazole mainly due to reduce toxicities and decreasing the hospital length of stay. In addition, PK-PD strategies that used infusion modifications to meropenem, piperacillin-tazobactam, ceftazidime, and cefepime, such as extended or continuous infusion, demonstrated important cost benefits, mainly due to reducing daily drug needs and lengths of hospital stays. Conclusions: TDM protocols and PK-PD empirically based prescriptions improve the cost-benefits and decrease the global hospital expenditures.